The effect of an escape room game on students’ academic self-efficacy and motivation for critical thinking: oncology nursing course - Betül Çakmak; Tuğçe Türten Kaymaz (BMC Nursing)
Abstract Objective This study investigated the effect of an escape room game on oncology nursing course students academic self-efficacy and motivation for critical thinking. Methods This study adopted a one-group pretest–posttest experimental research design. The sample consisted of forty-two nursing students. Data were collected using a personal information form, the Academic Nurses’ Self- Efficacy Scale, and the Critical Thinking Motivational Scale. The data were analyzed using descriptive statistics, t-test, Pearson-Spearman, Wilcoxon test. Results None of the nursing students had played an escape room game for educational purposes before (100%; n = 42). The escape room game helped nursing students develop academic self-efficacy and boosted their motivation for thinking critically respectively (t = -3.252, p = 0.002; Z = -2.027, p = 0.043). More than 90% of the students reported that the escape room game helped them understand the subject, retain information, and apply it effectively. Conclusion Universities should incorporate escape room games within the scope of oncology nursing courses as an alternative teaching approach to help students enhance their academic self-efficacy and critical thinking motivation. Researchers should plan studies with different samples to investigate the impact of escape room games on academic self-efficacy and critical thinking motivation.